Robustness Of The Standard Intuitionistic Fuzzy Sets For Image Enhancement - et. al., G. Leena Rosalind Mary, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper centered the robustness of the standard intuitionistic fuzzy sets which are recognized in the fuzzy as well as non-fuzzy regions of max – min intervals. The max-min and max-product composition of intuitionistic fuzzy relation (IFR) is discussed through intuitionistic fuzzy set (IFS). Each set changes its position with adaptive speed in a stochastic manner. Simultaneously index of fuzziness is measured by the amount of vagueness of IFS and classified according to max, min function. We extend these IFS to digital image enhancement techniques to obtain accurate information from the midst of vague images. Type I fuzzy set, establishes the region of ​​vague domains and range of images with its lower and upper membership degrees. Based on the lower and higher membership values, the discomposed membership degrees have fuzzy weighted average which represents the output image. The new output is imported into the main process of the fuzzy sets in order to find the adaptive and the best parameter according to its maximum and minimum level. Concurrently used to find the disparity between IFS is measured to optimize the decision making sense.